The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/ijms160922692
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Revealed the Embryo-Induced Gene Expression Patterns in the Endometrium from Meishan and Yorkshire Pigs

Abstract: The expression patterns in Meishan- and Yorkshire-derived endometrium during early (gestational day 15) and mid-gestation (gestational days 26 and 50) were investigated, respectively. Totally, 689 and 1649 annotated genes were identified to be differentially expressed in Meishan and Yorkshire endometrium during the three gestational stages, respectively. Hierarchical clustering analysis identified that, of the annotated differentially expressed genes (DEGs), 73 DEGs were unique to Meishan endometrium, 536 DEGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…However, the other two genes GLP1R and LRP1B had no expression in these two tissues from the above data. The APOB gene had very low expression in porcine endometrium during early (gestational day 15) and mid-gestation (gestational days 26 and 50) [ 60 , 62 ]. Based on the Yorkshire endometrium RNA-seq deep sequencing results (Size = 10Gb, unpublished data from our group), the AACS gene was highly expressed in the endometrium during early embryo implantation (RPKM > 250) and the expression of APOB gene was sharply increased at gestational day 15 (RPKM = 16.72) compared with day 12 (RPKM = 1.60).…”
Section: Resultsmentioning
confidence: 99%
“…However, the other two genes GLP1R and LRP1B had no expression in these two tissues from the above data. The APOB gene had very low expression in porcine endometrium during early (gestational day 15) and mid-gestation (gestational days 26 and 50) [ 60 , 62 ]. Based on the Yorkshire endometrium RNA-seq deep sequencing results (Size = 10Gb, unpublished data from our group), the AACS gene was highly expressed in the endometrium during early embryo implantation (RPKM > 250) and the expression of APOB gene was sharply increased at gestational day 15 (RPKM = 16.72) compared with day 12 (RPKM = 1.60).…”
Section: Resultsmentioning
confidence: 99%
“…In the past several breed-specific DEGs in porcine endometrium during early pregnancy were also reported [6,46]. For instance, the comparison of endometrium at 12D of early pregnancy between Meishan and Yorkshire [6] allowed to find 17,076 microarray probe-sets in at least two Affymetrix arrays and a total of 14,951 and 14,558 DEG-transcript-probes were identified in Meishan and Yorkshire endometrium respectively.…”
Section: Identification Of Deg Transcripts In Porcine Endometrium Durmentioning
confidence: 99%
“…In our study, we have found 43,603 probe-sets "present" in at least all three pooled arrays and a total of 6049 (3665 upregulated and 2384 downregulated) (Table S5), 374 (184 upregulated and 190 downregulated) (Table S7) and 6034 (2166 upregulated and 3868 downregulated) (Table S9), during 9D vs. 12D, 9D vs. 16D and 12D vs. 16D of early pregnancy in PLW gilts. In another study on breed-specific gene expression comparison of the endometrium [46], during early gestation [15D] vs. mid-gestation period [26D and 50D], revealed a total of 689 and 1649 annotated genes to be differentially expressed in Meishan and Yorkshire endometrium. This study allowed further annotation of DEGs and 73 of them were unique to Meishan endometrium, 536 were unique to Yorkshire endometrium and 228 DEGs were common in Meishan and Yorkshire endometrium.…”
Section: Identification Of Deg Transcripts In Porcine Endometrium Durmentioning
confidence: 99%
“…Previous studies show that Meishan pigs have less embryo loss than other commercial breeds, not only during early gestation but also mid-late gestation [4,5,19]. The studies conducted using microarrays and RNA-seq to identify and characterize the genes and miRNAs expressed in the uterine endometrium during early gestation [20][21][22][23] are an important step toward understanding the complex processes that govern the establishment and maintenance of pregnancy. However, little is known about genes and miRNAs expressed in the uterine endometrium during mid-late gestation.…”
Section: Introductionmentioning
confidence: 99%